2020
DOI: 10.3390/jcm9041095
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Triacylglycerol Content and Elevated Contents of Cell Membrane Lipids in Colorectal Cancer Tissue: A Lipidomic Study

Abstract: Recent evidence suggests that lipid composition in cancer tissues may undergo multiple alterations. However, no comprehensive analysis of various lipid groups in colorectal cancer (CRC) tissue has been conducted thus far. To address the problem in question, we determined the contents of triacylglycerols (TG), an energetic substrate, various lipids necessary for cell membrane formation, among them phospholipids (phosphatidylcholine, phosphatidylethanolamine), sphingolipids (sphingomyelin) and cholesterol (free,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 41 publications
10
42
0
Order By: Relevance
“…Note that TAG species with long chain acyl moieties, such as TAG 18:1-18:1-16:0, which accounted for the majority in the total TAG fraction, were significantly decreased in CRC tissues (Fig. 3A), supporting the previous result that the level of TAG was lower in CRC compared with normal tissues 10 . It has also been shown that the amount of total VLCFA, including esterified and nonesterified forms, was elevated in the sera of patients with CRC 11 .…”
Section: Discussionsupporting
confidence: 87%
“…Note that TAG species with long chain acyl moieties, such as TAG 18:1-18:1-16:0, which accounted for the majority in the total TAG fraction, were significantly decreased in CRC tissues (Fig. 3A), supporting the previous result that the level of TAG was lower in CRC compared with normal tissues 10 . It has also been shown that the amount of total VLCFA, including esterified and nonesterified forms, was elevated in the sera of patients with CRC 11 .…”
Section: Discussionsupporting
confidence: 87%
“…Some studies indicate that certain FA levels change depending on the stage of disease ( 5 ). Recently, our study confirmed these observations and showed other alterations in the FA profile in colorectal cancer tissue ( 9 ). Fatty acid profile alterations, such as the presence of cerotic acid ( 6 ) and decrease in the concentration of hydroxylated, polyunsaturated ultra-long-chain fatty acids ( 10 ), can also be found in the sera of CRC patients.…”
Section: Introductionsupporting
confidence: 86%
“…In contrast, in cancer tissue, 18:1 was observed in smaller amounts than those in normal mucosa. Our recent study suggests that this may be due to the high energy requirement of cancer cells during their rapid proliferation; 18:1, which is found in TAG, undergoes intensive β-oxidation as an energy source in CRC cells ( 9 ). We also found lower levels of ALA and a trend toward a decrease in LA.…”
Section: Discussionmentioning
confidence: 99%
“…In serum, there were noticeable increases in triglycerides containing C15:0,18:0, 18:1,18:2 and 18:3 [ 53 , 54 ] or decreases in lipids with C22:0, 24:0, 26:0, 30:0 and 18:1 [ 16 ]; and decreases in ultralong chain fatty acids [ 34 ]; increases in endocannabinoids and ceramides, sphingomyelins, eicosanoids [ 8 , 31 , 43 , 46 ], succinate, dimetihylguanosine, adenine, citraconic acid and methylguanosine [ 40 ]. Cerotic acid may also be a novel serum metabolic marker of colorectal malignancies [ 55 ], as well as plasma triacylglycerols [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%